MENINGKATKAN KEMAMPUAN PERKALIAN BILANGAN BULAT 6-10 MELALUI METODE JARIMATIKA BAGI ANAK TUNARUNGU - Sri - Mulyani (Universitas Negeri Padang, 2013)
Increases Ability Integer Multiplication 6 s / d 10 through Jarimatika Methods for Deaf Children in Class V SLB Tanjungpinang Affairs. ThesisPLBFIPUniversitasPadangDistrict.This research background in which deaf children experience difficulties in fifth grade arithmetic operations of multiplication number six and above. This is because children get bored and switch attention to enumerate through the media sticks or lines and abacus seeds too much. Thus the aim of this research is to improve the ability of multiplication for deaf children in class V SLB Tanjungpinang Affairs. Type of research is a classroom action research (action research) is done in the form of collaboration with classroom teachers. This action is done to the seven children who were the subject of research that deaf children class V SLB Tanjungpinang Affairs. The results showed that six sessions in the learning process which begins with jarimatika jarimatika forwarded using the arithmetic multiplication operation showed good results. Based on the average value obtained by the students at the end of the first cycle can be seen that reaches an average of 60%, average of reaches an average of 100%. It was concluded that the method could improve the ability of multiplication jarimatika